Towards Better Outcomes for Children and Families: Evaluation of the Implementation of an Outcomes Framework - Flynn, Susan; Caffrey, Louise; Spratt, Trevor; Holt, Stephanie (My University, 2024)
Background: The study is a result of the partnership between Trinity College Dublin and Tusla, the Child and Family Agency, supported by New Foundations within the Irish Research Council. The primary objective of this study was to evaluate the implementation of an outcomes framework designed for the Area Based Childhood (ABC) programme. This study was particularly geared towards understanding the facilitators and the barriers to the successful implementation of the outcomes framework across the 12 key locations where ABC services are based, hereafter called ‘ABC sites’. Therefore, the participants of this study were staff members of ABC service sites who had the experience of implementing the outcomes framework within their organisation. This executive summary will present a comprehensive, yet concise outline of the project. Methods: This project used a mixed methods approach to meet the research objective. The study consisted of two dependent phases of data collection. First, two qualitative focus group discussions were conducted independently – with a group of five managerial staff and a group of seven front-line staff respectively. Data from the focus group discussions were analysed and broken down into themes. These findings were then used to design a survey for the second phase of data collection. The survey was circulated to all ABC programme staff members though a gatekeeper. The results of the survey were analysed. A summary of findings of the study will be presented below. Key findings: As established by previous research, staff members expressed mixed views towards the outcomes framework. They perceived the framework to be moderately useful and indicated moderate comfort in using it in their work. Staff believed that the outcomes framework is a good tool to measure the impact of the ABC programme and standardise it. However, they also expressed concerns about the framework’s capacity to capture a well-rounded image of the services. They were also worried about the possibility of producing misleading results due to implementation errors and that it could take away the flexibility of their work.
PUBLISHED